Surface, microstructure, and tensile deformation characterization of LPBF SS316L microstruts micromachined with femtosecond laser - Abhi Ghosh; Sanchari Biswas; Tiffany Turner; Anne-Marie Kietzig; Mathieu Brochu (Materials & Design, 2021)
Considerable surface roughness, dimensional deviation, and non-uniform microstructure are a few of the characteristics found on thin or micro-scale features fabricated via laser powder bed fusion (LPBF) that yield inferior and/or inconsistent mechanical properties. Femtosecond laser micromachining can aid in fabricating micro-scale parts with ultra-high dimensional precision. In this work, the surface and tensile behavior of microstruts of 500μm nominal diameter micromachined with Gaussian laser pulses of <100fs duration are characterized. Roughness parameters such as Ra=0.9±0.2μm and Rz=3.4±1.3μm are achieved on the micromachined faces. Surface-associated grains are successfully ablated with negligible microstructural damage to the microstruts. As a result, the average uniform strain under quasi-static tensile loading is measured as 0.54±0.02 compared to 0.42±0.01 for the as-built microstruts. Uniform and non-uniform deformation strain portions are separated analytically and characterized primarily via in-situ imaging. Progressive degradation of the surface and dimensional variance is observed on the micromachined test specimens. Post necking initiation, ablation-associated asperities on the micromachined surfaces evolve into notches, leading to tensile failure.